Growth Patterns After Kidney Transplantation in European Children Over the Past 25 Years: An ESPN/ERA-EDTA Registry Study. Issue 1 (January 2020) - Bonthuis, Marjolein; Groothoff, Jaap W.; Ariceta, Gema; Baiko, Sergey; Battelino, Nina; Bjerre, Anna; Cransberg, Karlien; Kolvek, Gabriel; Maxwell, Heather; Miteva, Polina; Molchanova, Maria S.; Neuhaus, Thomas J.; et al.
Abstract : Background: Improved management of growth impairment might have resulted in less growth retardation after pediatric kidney transplantation (KT) over time. We aimed to analyze recent longitudinal growth data after KT in comparison to previous eras, its determinants, and the association with transplant outcome in a large cohort of transplanted children using data from the European Society for Paediatric Nephrology/European Renal Association and European Dialysis and Transplant Association Registry. Methods: A total of 3492 patients transplanted before 18 years from 1990 to 2012 were included. Height SD scores (SDS) were calculated using recent national or European growth charts. We used generalized equation models to estimate the prevalence of growth deficit and linear mixed models to calculate adjusted mean height SDS. Results: Mean adjusted height post-KT was −1.77 SDS. Height SDS was within normal range in 55%, whereas 28% showed moderate, and 17% severe growth deficit. Girls were significantly shorter than boys, but catch-up growth by 5 years post-KT was observed in both boys and girls. Children <6 years were shortest at KT and showed the greatest increase in height, whereas there was no catch-up growth in children transplanted >12. Conclusions: Catch-up growth post-KT remains limited, height SDS did not improve over time, resulting in short stature in nearly half of transplanted children in Europe.